The Role Of Women in The Work Forcecoffee Farming in Huta Ginjang Village Muara Distric Regency Of North Tapanuli - Silaban, Sartono; Tarumun, Suardi; Maharani, Evy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The research on the role of women in the workforce of coffee farming in Huta Ginjang village, Muara District, Regency of  North Tapanuli have been  done. The purpose of this study was to see how big the influence of social and economic factors on women's labor pouring in every stage of coffee farming jobs such as maintnance, harvesting and post-harvest. The method used in this study is  survey method and simple regression analysis. Data and information collected in this study using primary  and secondary data. Secondary data is data obtained from government agencies and the information obtained in the field while the primary data obtained directly from respondents by conducting interviews using a questionnaire tool. To see the outpouring of female labor in coffee farming is done through a multiple regression analysis with  indicator used is hours of work, days of work, and labor standards. Furthermore  analyzed using multiple linear regression analysis to see the impact of social  and economic factors in the outpouring of coffe farming workers whether significant  or effect is not significant. The results showed that the work of women involved in farming coffee  work  with father  and children. However, the greatest percentage of time  provided by Mother  at 55,50 percent, followed by Father 34,75 percent and  smallest given by children at 9,75 percent. Social factors remained influence but not significant  on female labor force coffee farming  means that just under 7,8 percent. Economic factors  significant influence on coffee farming, meaning that the influence of economic factors above 67,7 percent in coffee farming.   Keyword : Workforce, Farming, Women, Economic, Social.